Beneficial non-specific effects of live vaccines against COVID-19 and other unrelated infections - Aaby, Peter; Netea, Mihai G; Benn, Christine S (The Lancet infectious diseases, 2023)
Live attenuated vaccines could have beneficial, non-specific effects of protecting against vaccine-unrelated infections, such as BCG protecting against respiratory infection. During the COVID-19 pandemic, testing of these effects against COVID-19 was of interest to the pandemic control programme. Non-specific effects occur due to the broad effects of specific live attenuated vaccines on the host immune system, relying on heterologous lymphocyte responses and induction of trained immunity. Knowledge of non-specific effects has been developed in randomised controlled trials and observational studies with children, but examining of whether the same principles apply to adults and older adults was of interest to researchers during the pandemic. In this Personal View, we aim to define a framework for the analysis of non-specific effects of live attenuated vaccines against vaccine-unrelated infections with pandemic potential using several important concepts. First, study endpoints should prioritise severity of infection and overall patient health rather than incidence of infection only (eg, although several trials found no protection of the BCG vaccine against COVID-19 infection, it is associated with lower overall mortality than placebo). Second, revaccination of an individual with the same live attenuated vaccine could be the most effective strategy against vaccine-unrelated infections. Third, coadministration of several live attenuated vaccines might enhance beneficial non-specific effects. Fourth, the sequence of vaccine administration matters; the live attenuated vaccine should be the last vaccine administered before exposure to the pandemic infection and non-live vaccines should not be administered afterwards. Fifth, live attenuated vaccines could modify the immune response to specific COVID-19 vaccines. Finally, non-specific effects of live attenuated vaccines should always be analysed with subgroup analysis by sex of individuals receiving the vaccines.